Emmanuel Arua Ijere, Inland Town, Onisha Sate, Nigeria: - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
'We want to produce Sweetened Condensed Milk andUnsweetened Evaporated Milk, based on Soy milk (60%) and cows' milk (40%). Both products will be packaged in 150mlplastic sachets and 350ml plastic bottles, to make the products affordable to the...